The art of steer feeding - Cottrell, Amos Luther (My University, 1903)
Introduction: We say art of feeding because we intend to treat to treat the subject from the standpoint of the successful administration of the details which go to make the business profitable. We say that successful steer feeding is an art which cannot be attained by all, since a successful feeder must be acquainted with animals, feed, markets and above all must be possessed of rare insight and judgment that will enable him to solve many problems that arise. Cattle feeding has been indulged in from time immemorial. We are told of the killing of the fattened cattle on the return of prodigal. In early biblical history the burnt offerings were made from the fattling of the flocks and herds. Although no record is given as to the particular manner of fattening yet feeding must have been carried on in some form. The feeds used at that period were probably barley, flax and other grains that were native of that country. Some of the tribes of Israel were noted for their large herds and flocks and must necessarily have had some method of feeding. Tin modern times the business has become one of enormous magnitude involving millions of dollars’ worth of property and has for its ultimate end the furnishing of food for millions of people. Texas alone, according to the census of 1900, had 9,595,611 head of cattle, and a greater majority of the states have over half a million head within their borders. Thus the boundless resources of this business. The net worth of this industry amounts to startling figures. These statements give us something of an idea of the extent of responsibility that rests on those engaged in the occupation of steer feeding. The practical destination of all cattle is the block and as to the degree of excellence with which they should meet this end is determined by the feeder.
Citation: Cottrell, Amos Luther. The art of steer feeding. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Kind of Steers to Buy; Feed Lots; Feeding Aparatus; Theses